Students response system using smartphone for think-pair-share technique / Aainaa Hazwani Mohd Hashim - Mohd Hashim, Aainaa Hazwani (2017)
Generally, national school nowadays each classroom will consist of 30 to 40 students. Integratimng cooperative learning in education is the most frequently imply. Cooperative learning strategy is a learning process that will involve a group of students to work together on completing a task.